Lipophilicity determination of acidic compounds: MEEKC as a reliable high-throughput methodology - Xavier Subirats; Lidia Redón; Martí Rosés (International Association of Physical Chemists (IAPC), 2018)
In the present study a pressure-assisted MEEKC method with reversed-polarity using a conventional CE instrument with UV detection and uncoated fused silica capillaries is validated as a high-throughput methodology for the lipophilicity determination of the neutral species of acidic compounds (pKa > 3.5). After the calibration of the system with four standard compounds of known log Po/w, mass distribution ratios (log kMEEKC) of new molecules can be directly converted into log Po/w values by means of a simple linear equation (log Po/w=a·log kMEEKC+b). The method was internally and externally validated for a log Po/w range between -1.54 and 4.75, with higher accuracies than conventional liquid chromatographic methods.